Трансплантация экономических институтов: сущность и актуальные проблемы - Kataeva O. S. (Экономика и управление: проблемы, тенденции, перспективы развития, 2015)
This article is devoted the process of transplant (transplant) economic institutions. Globalization calls the economies of all countries, and economic institutions of different countries are embedding in the economic system of the countries with different economic development. This phenomenon is used to bring the system of economic institutions in different countries to the world standards. Equalize them. Usually cutting the unique features of the country during the transplantation process.
Keywords: трансплантация института; экономические институты; пересадка институтов; эффективность процесса глобализации; institutions' transplantation; economic institutions; the efficiency of the transplantation process